Implementation of the STAD Type Cooperative Learning Model in Physical Education Learning Through Mini Volleyball Games - Nawir, Nukhrawi (Sains Global Institut, Indonesia, 2025)
This study aims to analyze the effectiveness of the STAD type of Cooperative Learning model in Physical Education learning on mini volleyball material at SMP Negeri 17 Makassar. The study used a quasi-experimental design with a one-group pretest–posttest model involving 20 students as a sample. The research instruments included a mini volleyball basic technique skills test, an active participation observation sheet, and a learning motivation questionnaire. Data were analyzed using descriptive statistics and a paired sample t-test. The results showed a significant increase in three main variables. First, basic technique skills experienced an average increase from 52.6 to 71.7 after the implementation of the STAD model. Second, student active participation increased by 31%, indicating that cooperative learning encourages positive engagement and interaction between group members. Third, student learning motivation increased by 30.1%, indicating that group rewards, cooperation, and a pleasant learning atmosphere can increase students' intrinsic motivation to participate in learning. Statistical tests showed that all of these increases were significant (p < 0.05). These findings confirm that the STAD model is effective in physical education (PJOK) learning, particularly in games that require cooperation, such as mini volleyball. The study recommends broader implementation of this model in schools and the use of more robust experimental designs in future research.